Rotatron sleeve patch as well as preparation method and application thereof

By using gradient structures loaded with connective tissue growth factor and calcium silicate in rotator cuff patches, the shortcomings in mechanical properties and biological activities of existing rotator cuff patches are solved, and effective healing and regeneration of the rotator cuff tendon-bone interface is achieved.

CN119746152AActive Publication Date: 2025-04-04NANKAI UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411936358.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The existing rotator cuff patches have shortcomings in terms of mechanical properties and biological activity, which leads to a high risk of re-tearing after rotator cuff repair, and the biological function of the material is insufficient, affecting the healing effect.

Method used

A gradient structure rotator cuff patch with a loaded connective tissue growth factor and calcium silicate was used to prepare polymer nanofiber patches by electrospinning, and calcium silicate nanoparticles were co-precipitated in situ at the distal end of the patch, and connective tissue growth factor was loaded at the proximal end of the patch to form a gradient composite structure.

Benefits of technology

The mechanical properties and biological activity of rotator cuff patches are improved, multi-tissue regeneration of tendons, cartilage and bones are promoted, and the healing of the tendon-bone interface is synchronized, significantly reducing the risk of re-tearing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746152A_ABST
    Figure CN119746152A_ABST
Patent Text Reader

Abstract

The invention discloses a rotator cuff patch as well as a preparation method and application thereof, and belongs to the technical field of composite biological materials of medical engineering.The preparation method comprises the following steps: preparing an oriented nanofiber patch co-spun by a synthetic biodegradable high polymer and a natural bioactive protein of a biological source through electrostatic spinning; calcium silicate nanoparticles are co-precipitated in situ at the far end of the oriented nanofiber patch, connective tissue growth factors are loaded at the near end of the oriented nanofiber patch, and the rotator cuff patch is obtained and is provided with a tendon promoting area loaded with the connective tissue growth factors. The gradient composite rotator cuff patch with a cartilage promoting area co-loaded by connective tissue growth factors and calcium silicate and a bone promoting area deposited by calcium silicate can be used for treating acute rotator cuff tearing, multi-tissue regeneration of tendons, cartilages and bones is effectively promoted, tendon-bone interface healing is synchronously completed, and rotator cuff injury repairing is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite biomaterials in biomedical engineering, and in particular relates to a rotator cuff patch and a preparation method and application thereof. Background Art

[0002] Rotator cuff tear is a common musculoskeletal disease that usually causes severe shoulder pain and limited functional activities. Surgical repair of the damaged rotator cuff through arthroscopic technology is an effective means of treating rotator cuff tears. However, the incidence of re-tear after rotator cuff repair surgery is 26.6%-94.0%, and the re-tear rate is still relatively high. The regeneration capacity of the gradient component from tendon to bone is limited. The mechanical properties of the tendon-bone interface restored after surgery are much worse than those of the normal fibrocartilaginous tendon-bone healing structure, which will eventually lead to poor healing of the tendon-bone interface and re-tear. The large stress concentration at the tendon-bone interface is considered to be the main cause of re-tear after rotator cuff repair. The patch can serve as a mechanical support structure during the rotator cuff repair process to disperse the stress concentration at the interface. The use of the patch to enhance the fixation between the tendon and the bone can prevent the rotator cuff from tearing again after repair. It is currently considered to be a promising treatment strategy.

[0003] However, the existing rotator cuff patches still have the following problems: First, the mechanical properties of the patches cannot adapt to the regeneration needs of natural tissues. The mechanical properties of the patch play an important role in the healing of the tendon-bone interface. If the mechanical properties of the patch are insufficient, it may fail prematurely; if the elasticity of the patch is insufficient, it may hinder tissue growth due to stress shielding. When the shoulder joint moves, the patch will stretch with the tendon. Therefore, the patch needs to have a good tensile load to withstand the tension caused by the tendon activity to prevent premature rupture and failure due to insufficient mechanical properties. The patch also needs to have good elasticity to conform to the dynamic process of tendon stretching and rebound during tendon stretching to avoid hindering the normal movement of the rotator cuff. Second, the patch lacks bioactivity and functionality. The bioactivity and functionality of the patch material used to repair rotator cuff injuries are key factors for the successful repair of the tendon-bone interface. The patch material first needs to have good in vivo compatibility to ensure that endogenous cells adhere, survive, and proliferate on its surface. Rotator cuff patches with poor activity may cause some complications, such as infection and rejection. The lack of biological functionality is often manifested as insufficient ability of the patch to promote multidirectional cell differentiation, which will affect the synchronous regeneration of multiple tissues at the tendon-bone interface, and ultimately lead to limited healing of the injured site after rotator cuff repair.

[0004] Therefore, it is necessary to provide a rotator cuff patch with bionic mechanical properties and gradient-induced tendon-bone interface regeneration. Summary of the invention

[0005] In order to solve the above technical problems, the present invention proposes a rotator cuff patch and its preparation method and application. The rotator cuff patch is fixed to the damaged tendon-bone interface by suturing. One end of the rotator cuff patch is sutured to the supraspinatus muscle, which is defined as the proximal end of the patch; the other end is fixed to the humerus, which is defined as the distal end of the patch. The rotator cuff patch of the present invention is a gradient structure rotator cuff patch loaded with connective tissue growth factor and calcium silicate. The oriented nanofiber patch co-spun by synthetic biodegradable polymer and natural bioactive protein of biological origin is prepared by electrospinning. Calcium silicate nanoparticles are in situ co-precipitated at the distal end of the patch, connective tissue growth factor is loaded at the proximal end of the patch, and the protein is connected to the connective tissue growth factor through hydrogen bonds, and finally a gradient composite rotator cuff patch with a tendon-promoting area loaded with connective tissue growth factor, a cartilage-promoting area co-loaded with connective tissue growth factor and calcium silicate, and a bone-promoting area deposited with calcium silicate is prepared.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] One of the technical solutions of the present invention:

[0008] The present invention provides a method for preparing a rotator cuff patch. An oriented nanofiber patch co-spun by a synthetic biodegradable polymer and a natural bioactive protein of biological origin is prepared by electrospinning, calcium silicate nanoparticles are in situ co-precipitated at the distal end of the oriented nanofiber patch, and connective tissue growth factor is loaded at the proximal end of the oriented nanofiber patch to obtain the rotator cuff patch.

[0009] The rotator cuff patch was fixed to the damaged tendon-bone interface by suture. One end of the rotator cuff patch was sutured to the supraspinatus muscle, defined as the proximal end of the patch; the other end was fixed to the humerus, defined as the distal end of the patch.

[0010] Connective tissue growth factor (CTGF) was first discovered by BRADHAM et al. in the conditioned culture medium of human umbilical vein endothelial cells in 1991. It is a cysteine-rich secretory peptide composed of 349 amino acids and with a molecular weight of 34 to 38 KD.

[0011] Furthermore, the method for preparing the rotator cuff patch comprises the following steps:

[0012] S1. Using synthetic biodegradable polymers and natural bioactive proteins of biological origin as raw materials and hexafluoroisopropanol as solvent, an oriented nanofiber patch is prepared by electrospinning. Because the nanofibers in the present invention are arranged in a directional pattern rather than randomly distributed, which is similar to the parallel arrangement of tendon fibers, it is called an "oriented nanofiber patch";

[0013] S2. vertically immersing the distal end of the oriented nanofiber patch in a tetrahydrate calcium nitrate solution, and freeze-drying the patch after the reaction. In this step, calcium ions form coordination bonds with carbonyl and carboxyl groups in natural biologically active proteins of biological origin and bind to the surface of the nanofiber patch;

[0014] S3. The distal end of the nanofiber patch obtained in S2 is vertically immersed in a sodium silicate nonahydrate solution, and freeze-dried after the reaction to obtain a gradient patch with calcium silicate loaded at the distal end. In this step, silicate ions combine with calcium ions, and calcium silicate nanoparticles are in situ deposited on the surface of the nanofibers (the reaction equation is: Ca(NO3)2+Na2SiO3→CaSiO3↓+2NaNO3). Through the capillary effect and the gravity of the solution, more calcium silicate is deposited on the patch near the distal end, while relatively less calcium silicate is distributed on the patch near the proximal end, so a gradient patch with calcium silicate loaded at the distal end is obtained;

[0015] S4. The proximal end of the gradient patch prepared in S3 is vertically immersed in a connective tissue growth factor solution, freeze-dried after the reaction, and the connective tissue growth factor is loaded on the proximal end of the gradient patch to obtain the rotator cuff patch. In this step, the proximal end of the gradient patch is vertically immersed in a connective tissue growth factor solution for reaction, and hydrogen bonds are formed between the connective tissue growth factor protein and the natural biologically active protein of biological origin. Through the capillary effect and the gravity of the solution, the patch close to the proximal end absorbs more connective tissue growth factor, while the patch close to the distal end absorbs relatively less connective tissue growth factor, and finally a gradient structure rotator cuff patch loaded with connective tissue growth factor and calcium silicate is obtained.

[0016] In the method of the present invention, synthetic biodegradable polymer and natural biologically active protein of biological origin are used as raw materials, hexafluoroisopropanol is used as solvent, and the mixture is stirred for 6-10 hours to obtain electrospinning solution.

[0017] Exemplarily, the synthetic biodegradable polymer includes polycaprolactone, a copolymer of polylactide and caprolactone, or a copolymer of lactide and glycolide; and / or

[0018] The biologically derived natural bioactive protein includes at least one of collagen, keratin, fibrin and elastin, and is preferably type I collagen derived from bovine Achilles tendon.

[0019] Furthermore, the mass ratio of the synthetic biodegradable polymer to the natural bioactive protein of biological origin is (8-13.5):(1-3), for example, when the mass of the synthetic biodegradable polymer is 1.35 g, the mass of the natural bioactive protein of biological origin is 0.15 g.

[0020] Furthermore, the mass volume ratio of the synthetic biodegradable polymer and hexafluoroisopropanol is (0.8-1.35) g:10 mL.

[0021] Furthermore, during the electrospinning, the flow rate of the spinning solution is 2 mL / h, the working voltage is 14-16 kV, the distance between the syringe needle and the aluminum foil receiver is 14-16 cm, and the rotation speed of the aluminum foil receiver is 1500-2000 r / min. Preferably, the volume of the spinning solution is 4 mL, the flow rate of the spinning solution is 2 mL / h, the working voltage is 15 kV, the distance between the syringe needle and the aluminum foil receiver is 15 cm, and the rotation speed of the aluminum foil receiver is 1500 r / min.

[0022] After the electrospinning is completed, the prepared oriented nanofiber patch is placed in a vacuum dryer for 48 hours to fully remove the residual solvent on the fiber patch.

[0023] Furthermore, the concentration of the calcium nitrate tetrahydrate solution is 10-40 mmol / L. The reaction time in the calcium nitrate tetrahydrate solution is 2 hours, and the freeze-drying time after the reaction is completed is 24 hours.

[0024] Furthermore, the concentration of the sodium silicate nonahydrate solution is 10-40 mmol / L. The reaction time in the sodium silicate nonahydrate solution is 2 hours, and the freeze-drying time after the reaction is completed is 24 hours.

[0025] Furthermore, the concentration of the connective tissue growth factor solution is 100-200 ng / mL, the immersion time in the connective tissue growth factor solution is 22-26 hours, and the freeze-drying time after the reaction is completed is 24 hours.

[0026] The principle of the present invention is:

[0027] 1. Complementarity between synthetic biodegradable polymers and natural bioactive proteins from biological sources: Synthetic biodegradable polymers have good mechanical properties, showing the characteristics of high toughness and low elasticity, while some natural bioactive proteins from biological sources have good elasticity and can quickly recover to their original state after being subjected to external forces. Synthetic biodegradable polymers and natural bioactive proteins from biological sources will interact with each other during the electrospinning process, such as forming hydrogen bonds and van der Waals forces. These interactions help to enhance the bonding force between fibers, so that the mechanical properties of the rotator cuff patch are significantly improved.

[0028] 2. Physical and chemical properties of the patch surface: Synthetic biodegradable polymers usually exhibit strong hydrophobicity. The hydrophobic surface easily leads to protein denaturation, which is not conducive to cell adhesion and growth. After combining with natural bioactive proteins of biological origin, the hydrophilicity of the patch is improved, which enhances the cell affinity of the patch. The hydrophilic surface can adsorb more adhesion proteins. These proteins provide adhesion sites for cells, which is conducive to maintaining the conformation and activity of adhesion proteins, thereby enhancing the interaction with the material surface.

[0029] The second technical solution of the present invention:

[0030] The present invention also provides a rotator cuff patch prepared according to the method, which is a gradient structure rotator cuff patch loaded with connective tissue growth factor and calcium silicate.

[0031] The third technical solution of the present invention:

[0032] The present invention also provides application of the rotator cuff patch in preparing tendon-bone interface damage repair material.

[0033] Compared with the prior art, the present invention has the following advantages and technical effects:

[0034] 1. Preparation process: The raw materials of the patch prepared by the present invention are synthetic biodegradable polymers and natural bioactive proteins of biological origin. Synthetic biodegradable polymers (such as polycaprolactone) are commonly used biomedical materials, which have been approved by the US FDA and can usually be used as in vivo implant materials and drug controlled release materials; natural bioactive proteins of biological origin (such as collagen or keratin) have good biocompatibility and biodegradable safety, and have good immunogenicity. The present invention prepares the patch material by electrospinning, which has the characteristics of simple preparation process, mild preparation conditions, no toxic substances such as chemical cross-linking agents, and the prepared product is non-toxic and has high biocompatibility.

[0035] 2. Material properties: The patch prepared by the present invention uses polymer materials as the main raw materials, and the prepared patch has good mechanical properties. After adding a certain proportion of collagen or keratin, the mechanical properties of the patch are further significantly improved, and the high toughness and low elasticity characteristics of the polymer material are changed. The prepared patch has better performance in elastic modulus and tensile strength, can meet the mechanical load required in the rotator cuff tendon repair process, and effectively play a role in stress dispersion during the repair process.

[0036] 3. Product function: The rotator cuff patch prepared by the present invention is a multifunctional patch, which can achieve the function of inducing multidirectional differentiation of cells and promoting the repair and regeneration of multiple tissues by releasing two active substances. Connective tissue growth factor and calcium silicate with significant pro-regeneration effects are selected for the repair of tendon tissue and bone tissue respectively, and the synergistic effect of connective tissue growth factor and calcium silicate can more significantly promote the chondrogenic differentiation of cells. The loading of two active substances effectively promotes the repair of three gradient tissues, which is better than the repair effect achieved by loading three active substances in the past. It can be used for the treatment of acute rotator cuff tears, effectively promoting the regeneration of multiple tissues of tendons, cartilages and bones, and then synchronously completing the healing of the tendon-bone interface to promote the repair of rotator cuff injuries. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0038] Figure 1 This is a diagram of the mechanical properties of the rotator cuff patch of Example 1 of the present invention;

[0039] Figure 2 This is a diagram showing the effect of the rotator cuff patch in Example 1 of the present invention on promoting the healing of the rotator cuff tendon-bone interface in vivo;

[0040] Figure 3 This is a diagram showing the effect of the rotator cuff patch in Example 1 of the present invention on promoting fibrocartilage regeneration at the rotator cuff tendon-bone interface in vivo;

[0041] Figure 4 The figure is a diagram showing the effect of the rotator cuff patch in Example 1 of the present invention on promoting bone regeneration at the rotator cuff tendon-bone interface in vivo, A is the reconstruction and regeneration of new bone at the tendon-bone interface at 4 weeks and 8 weeks, B is the quantitative result of bone volume fraction at 4 weeks and 8 weeks, and C is the quantitative result of bone density at 4 weeks and 8 weeks;

[0042] exist Figure 2 and Figure 3 In the diagram, B stands for Bone. Bone is an important component when discussing the rotator cuff tendon-bone interface because it involves the connection between the tendon and the bone. I stands for Interface. In this case, it refers to the connection interface between the tendon and the bone (including uncalcified fibrocartilage and calcified fibrocartilage). This is a critical area because it involves the combination of two different types of tissue. T stands for Tendon. The rotator cuff tendons are a group of tendons of the shoulder rotator muscles. They connect the muscles to the bones and play an important role in shoulder movement. DETAILED DESCRIPTION

[0043] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0044] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0045] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0046] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0047] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0048] Unless otherwise specified, the normal temperature in the present invention is 25±2°C.

[0049] All raw materials used in the examples of the present invention are commercially available.

[0050] In the present invention, the rotator cuff patch is fixed to the tendon-bone interface by suturing, and the end of the rotator cuff patch contacting the supraspinatus tendon area is defined as the proximal end, and the end of the rotator cuff patch contacting the humeral area is defined as the distal end.

[0051] In some embodiments of the present invention, a method for preparing a rotator cuff patch is provided, comprising the following steps:

[0052] S1. A synthetic biodegradable polymer and a natural bioactive protein from a biological source are used as raw materials, hexafluoroisopropanol (HFIP) is used as a solvent, and the mixture is stirred for 6-10 hours to obtain an electrospinning solution, and an oriented nanofiber patch is prepared by electrospinning. The mass ratio of the synthetic biodegradable polymer to the natural bioactive protein from a biological source is (8-13.5): (1-3), and the preferred mass ratio is 9:1. For example, when the mass of the synthetic biodegradable polymer is 1.35 g, the mass of the natural bioactive protein from a biological source is 9:1. The weight volume ratio of the synthetic biodegradable polymer and hexafluoroisopropanol is (0.8-1.35) g: 10 mL; during electrospinning, when the volume of the spinning solution is 4 mL, the flow rate of the spinning solution is 2 mL / h, the working voltage is 15 kV, the distance between the syringe needle and the aluminum foil receiver is 15 cm, and the rotation speed of the aluminum foil receiver is 1500 r / min; after the electrospinning is completed, the prepared oriented nanofiber patch is placed in a vacuum dryer for 48 hours to fully remove the residual solvent on the fiber patch;

[0053] S2. vertically immerse the distal end of the nanofiber patch in a 10-40 mmol / L calcium nitrate tetrahydrate (Ca(NO3)2·4H2O) solution, react for 2 hours, and then freeze-dry for 24 hours. In this step, calcium ions form coordination bonds with carbonyl and carboxyl groups in natural biologically active proteins of biological origin and bind to the surface of the nanofiber patch;

[0054] S3. The distal end of the nanofiber patch obtained in S2 is vertically immersed in a sodium silicate nine hydrate (Na2SiO3·9H2O) solution with a concentration of 10-40mmol / L, reacted for 2h and then freeze-dried for 24h to obtain a gradient patch with calcium silicate (CS) loaded at the distal end. In this step, silicate ions combine with calcium ions, and calcium silicate nanoparticles are in situ deposited on the surface of the nanofibers (the reaction equation is: Ca(NO3)2+Na2SiO3→CaSiO3↓+2NaNO3). Through the capillary effect and the gravity of the solution, more calcium silicate is deposited on the patch near the distal end, while relatively less calcium silicate is distributed on the patch near the proximal end. Therefore, a gradient patch with calcium silicate loaded at the distal end is obtained.

[0055] S4. The proximal end of the gradient patch prepared in S3 is vertically immersed in a connective tissue growth factor (CTGF) solution with a concentration of 100-200 ng / mL, reacted for 22-26 hours and then freeze-dried for 24 hours, and the connective tissue growth factor is loaded on the proximal end of the gradient patch to obtain the rotator cuff patch. In this step, the proximal end of the gradient patch is vertically immersed in the connective tissue growth factor solution for reaction, and hydrogen bonds are formed between the connective tissue growth factor protein and the natural biologically active protein of biological origin. Through the capillary effect and the gravity of the solution, the patch close to the proximal end absorbs more connective tissue growth factor, while the patch close to the distal end absorbs relatively less connective tissue growth factor, and finally a gradient structure rotator cuff patch loaded with connective tissue growth factor and calcium silicate is obtained.

[0056] In some embodiments of the present invention, the synthetic biodegradable polymer includes polycaprolactone (PCL), polylactide and caprolactone copolymer or lactide and glycolide copolymer, preferably polylactide and caprolactone copolymer is poly L-lactide-caprolactone (PLCL), preferably PCL; the natural bioactive protein of biological origin includes at least one of collagen, keratin, fibrin and elastin, for example, the natural bioactive protein of biological origin is bovine Achilles tendon-derived collagen type I (COLⅠ) and wool-derived keratin (KRT), preferably COLⅠ. Synthetic biodegradable polymers have good mechanical properties, showing the characteristics of high toughness and low elasticity, while some natural bioactive proteins of biological origin have good elasticity and can quickly recover to their original state after being subjected to external forces. Synthetic biodegradable polymers and natural bioactive proteins of biological origin will interact with each other during the electrospinning process, such as forming hydrogen bonds, van der Waals forces, etc. These interactions help to enhance the bonding force between fibers, so that the mechanical properties of the composite fibers (oriented nanofiber patches) are significantly improved. In the following typical embodiments of the present invention, PCL, PLCL, COLⅠ and KRT are taken as examples for description.

[0057] The abbreviations involved in the following embodiments specifically refer to:

[0058] PCL: polycaprolactone;

[0059] PLCL: poly-L-lactide-caprolactone;

[0060] COLⅠ: Type Ⅰ collagen from bovine Achilles tendon;

[0061] KRT: Wool derived keratin

[0062] HFIP: hexafluoroisopropanol;

[0063] CS: calcium silicate;

[0064] CTGF: connective tissue growth factor;

[0065] PC: PCL / COLⅠ;

[0066] PLC:PLCL / COLⅠ;

[0067] PK: PCL / KRT;

[0068] PLK:PLCL / KRT;

[0069] PC@CTGF / CS: PCL / COLⅠ patch loaded with calcium silicate at the distal end and connective tissue growth factor at the proximal end.

[0070] PLC@CTGF / CS: PLCL / COLⅠ patch loaded with calcium silicate at the distal end and connective tissue growth factor at the proximal end.

[0071] PK@CTGF / CS: PCL / KRT patch loaded with calcium silicate at the distal end and connective tissue growth factor at the proximal end.

[0072] PLK@CTGF / CS: PLCL / KRT patch loaded with calcium silicate at the distal end and connective tissue growth factor at the proximal end.

[0073] It should be pointed out that the matters not described in detail in the present invention are conventional operating means in the art and are not the focus of the present invention.

[0074] The technical solution of the present invention is further illustrated by the following embodiments.

[0075] Example 1

[0076] A preparation method of a rotator cuff patch loaded with connective tissue growth factor and calcium silicate at both ends:

[0077] 1) Preparation of PC electrospinning solution:

[0078] 1.35 g PCL and 0.15 g COLⅠ were dissolved in 10 mL HFIP and stirred for 8 h to obtain a 15 wt % PC solution with a PCL:COLⅠ ratio of 9:1 (mass ratio).

[0079] 2) Preparation of PC electrospinning patch:

[0080] Take 4 mL of PC solution, set the flow rate of the spinning solution to 2 mL / h, the working voltage to 15 kV, the distance between the syringe needle and the aluminum foil receiver to 15 cm, and the rotation speed of the aluminum foil receiver to 1500 r / min. After the electrospinning is completed, a PC patch is obtained. The obtained PC patch is placed in a vacuum dryer and dried for 48 hours to fully remove the residual solvent on the PC patch.

[0081] 3) Preparation of PC@CTGF / CS composite patch:

[0082] The distal end of the PC patch obtained in step 2) is placed in a 10 mmol Ca(NO3)2·4H2O solution, immersed in a vacuum condition for 2 h, treated in a vacuum dryer for 24 h, immersed in a 10 mmol Na2SiO3·9H2O solution under vacuum conditions for 2 h, and treated in a vacuum dryer for 24 h to obtain a PC patch with CS loaded at the distal end; the proximal end of the PC patch with CS loaded at the distal end is placed in a 100 ng / mL CTGF solution, immersed at 4°C for 24 h, and treated in a freeze dryer for 24 h to finally obtain a PC@CTGF / CS composite patch.

[0083] Example 2

[0084] A preparation method of a rotator cuff patch loaded with connective tissue growth factor and calcium silicate at both ends:

[0085] 1) Preparation of PLC electrospinning solution:

[0086] 1.35 g PLCL and 0.15 g COLⅠ were dissolved in 10 mL HFIP and stirred for 8 h to obtain a 15 wt % PLC solution with a PLCL:COLⅠ ratio of 9:1 (mass ratio).

[0087] 2) Preparation of PLC electrospinning patch:

[0088] Take 4 mL of PLC solution, set the flow rate of the spinning solution to 2 mL / h, the working voltage to 15 kV, the distance between the syringe needle and the aluminum foil receiver to 15 cm, and the rotation speed of the aluminum foil receiver to 1500 r / min. After the electrospinning is completed, a PLC patch is obtained. The obtained PLC patch is placed in a vacuum dryer for 48 hours to fully remove the residual solvent on the PLC patch.

[0089] 3) Preparation of PLC@CTGF / CS composite electrospun patch:

[0090] The distal end of the PLC patch obtained in step 2) was placed in 10mmol Ca(NO3)2·4H2O, immersed in vacuum for 2h, treated in a vacuum dryer for 24h, immersed in 10mmol Na2SiO3·9H2O under vacuum for 2h, and treated in a vacuum dryer for 24h to obtain a PLC patch loaded with CS at the distal end. The proximal end of the PLC patch loaded with CS at the distal end was placed in a 100ng / mL CTGF solution, immersed at 4°C for 24h, and treated in a freeze dryer for 24h to finally obtain a PLC@CTGF / CS composite patch.

[0091] Example 3

[0092] A preparation method of a rotator cuff patch loaded with connective tissue growth factor and calcium silicate at both ends:

[0093] 1) Preparation of PK electrospinning solution:

[0094] 1.35 g PCL and 0.3 g KRT were dissolved in 10 mL HFIP and stirred for 8 h to obtain a 16.5 wt% PK solution.

[0095] 2) Preparation of PK electrospinning patch:

[0096] Take 4 mL of PK solution, set the flow rate of the spinning solution to 2 mL / h, the working voltage to 15 kV, the distance between the syringe needle and the aluminum foil receiver to 15 cm, and the rotation speed of the aluminum foil receiver to 1500 r / min. After the electrospinning is completed, a PK patch is obtained. The obtained PK patch is placed in a vacuum dryer for 48 hours to fully remove the residual solvent on the PK patch.

[0097] 3) Preparation of PK@CTGF / CS composite electrospun patch:

[0098] The distal end of the PK patch obtained in step 2) was placed in 40 mmol Ca(NO3)2·4H2O, immersed in vacuum for 2 h, and treated in a vacuum dryer for 24 h, and then immersed in 40 mmol Na2SiO3·9H2O under vacuum for 2 h, and treated in a vacuum dryer for 24 h to obtain a PK patch loaded with CS at the distal end. The proximal end of the PK patch was placed in a 200 ng / mL CTGF solution, immersed at 4°C for 24 h, and treated in a freeze dryer for 24 h to finally obtain a PK@CTGF / CS composite patch.

[0099] Example 4

[0100] A preparation method of a rotator cuff patch loaded with connective tissue growth factor and calcium silicate at both ends:

[0101] 1) Preparation of PLK electrospinning solution:

[0102] 0.8 g PLCL and 0.1 g KRT were dissolved in 10 mL HFIP and stirred for 8 h to obtain a 9 wt % PLK solution with a PLCL:KRT ratio of 8:1 (mass ratio).

[0103] 2) Preparation of PLK electrospinning patch:

[0104] Take 4 mL of PLK solution, set the flow rate of the spinning solution to 2 mL / h, the working voltage to 15 kV, the distance between the syringe needle and the aluminum foil receiver to 15 cm, the rotation speed of the aluminum foil receiver to 1500 r / min, and place the obtained PLK patch in a vacuum dryer for 48 hours to fully remove the residual solvent on the patch.

[0105] 3) Preparation of PLK@CTGF / CS composite electrospun patch:

[0106] The distal end of the PLK patch obtained in step 2) was placed in 20mmol Ca(NO3)2·4H2O, immersed in vacuum for 2h, treated in a vacuum dryer for 24h, immersed in 20mmol Na2SiO3·9H2O under vacuum for 2h, and treated in a vacuum dryer for 24h to obtain a PLK membrane loaded with CS at the distal end. The proximal end of the PLK patch was placed in a 100ng / mL CTGF solution, immersed at 4°C for 24h, and treated in a freeze dryer for 24h to finally obtain a PLK@CTGF / CS composite patch.

[0107] After testing, the performance of the patches prepared in the above Examples 1-4 is similar and there is no significant difference. The following is a performance description of the rotator cuff patch prepared in Example 1.

[0108] 1. Mechanical properties test of the patch

[0109] The mechanical properties were evaluated by a universal material testing machine. Each sample was cut into a rectangular strip with a length of 30 mm, a width of 10 mm, and a thickness of 0.2 mm. The tensile test was carried out at room temperature with a tensile speed of 10 mm / min. The sample was stretched until it broke. The elastic modulus, ultimate load, tensile strength, and elongation at break were recorded and calculated. The rotator cuff tendon-bone interface is repeatedly subjected to mechanical loads in daily life. Therefore, tensile resistance and elasticity are essential properties of the patch in the application of rotator cuff injury repair. The mechanical test results of the PC patch are shown in Figure 2. Figure 1 As shown in the figure, the average elastic modulus of the PC patch is 46.35±4.81MPa, which is 3.98 times that of the PCL patch; the average tensile strength is 23.59±1.88MPa, which is 4.77 times that of the PCL patch. The PC patch has better mechanical properties, which is enough to match the load of the natural supraspinatus tendon and can meet the needs of clinical applications.

[0110] 2. Tendon-bone interface healing effect

[0111] The rat rotator cuff acute tear model was established, and a longitudinal skin incision was made on the anterolateral side of the shoulder joint. The deltoid muscle was cut to expose the supraspinatus tendon, whose insertion point was attached to the greater tubercle of the humerus. The supraspinatus muscle was separated from the insertion using a No. 10 blade, and the exposed tendon-bone attachment point was gently peeled off to ensure that the supraspinatus tendon attachment was completely removed. A Kirschner wire with a diameter of 0.5 mm was used to establish two parallel bone tunnels from the tendon-bone attachment point to the lateral side of the humeral head. The end of the supraspinatus tendon was passed through the bone tunnel with a 3-0 suture, and the suture was tied to the humeral cortex. The corresponding patch was sutured above the tendon-bone repair site to form a "double-layer structure", with the proximal end of the patch fixed to the supraspinatus tendon and the distal end fixed to the humerus. The rotator cuff site of the Normal group was not treated in any way; the direct suture group was named the Suture group; the group repaired using the PC patch (the product of step 2 in Example 1) was named the PC group; the group repaired using the PC@CTGF / CS composite patch was named the PC@CTGF / CS group. After 4 and 8 weeks of in vivo repair, samples were collected for histological staining (H&E staining, Safranin O-Fast Green staining) and Micro-CT to verify the repair effect of the invented patch on the rotator cuff tendon-bone interface.

[0112] Hematoxylin-eosin staining results of tendon-bone interface Figure 2 As shown in the figure, at the initial 4 weeks of repair, the distribution of the tendon-bone interface in each group was discontinuous, which was different from the natural tissue, and the Suture group showed obvious inflammatory cell infiltration, while the inflammatory infiltration in the PC group and the PC@CTGF / CS group was relatively mild. As the repair time was extended to 8 weeks, the tendon-bone interface of each group further healed, and the inflammatory infiltration in each group was significantly alleviated. The tendon-bone interface of the PC@CTGF / CS group healed the best, with no obvious boundaries between the tissues, and the morphology of the healed tendon-bone interface was closer to the natural tissue.

[0113] 3. Fibrocartilage Regeneration Effect

[0114] Safranin fast green staining results are as follows Figure 3 The results show that the dark red dyed area at the tendon-bone interface refers to the extracellular matrix proteoglycans, and at different repair nodes, it is obvious that the production and deposition of glycosaminoglycans in the PC@CTGF / CS group are more than those in other groups, and the fibrocartilage regeneration in the PC@CTGF / CS group is better. The above results show that the double-end loaded connective tissue growth factor and calcium silicate patch prepared by the present invention effectively promotes the regeneration of fibrocartilage at the tendon-bone interface.

[0115] 4. New bone formation effect

[0116] Micro-CT was used to observe the reconstruction and regeneration of new bone at the tendon-bone interface. Figure 4As shown in A, at 4 and 8 weeks, the bone defect area in the Suture group was larger, and at 8 weeks, the bone regeneration in the PC group was better, but the new bone surface of the humerus was not smooth. Compared with the Suture group and the PC group, the new bone regeneration in the PC@CTGF / CS group was better, which was most similar to the normal group. There was no significant difference between the new bone tissue in the PC@CTGF / CS group and the surrounding normal tissue, and complete regeneration was basically achieved at 8 weeks. Figure 1 Figures B and C are the quantitative results of bone volume fraction (BV / TV) and bone mineral density (BMD) at 4 and 8 weeks, respectively. At 8 weeks, the BMD and BV / TV of the PC@CTGF / CS group were 1.49 and 1.14 times that of the Suture group, respectively. The above results indicate that the PC@CTGF / CS patch can significantly promote bone regeneration at the tendon-bone interface.

[0117] In summary, the present invention successfully prepared a rotator cuff patch PC@CTGF / CS with double-end load of connective tissue growth factor and calcium silicate. The patch can cover the damaged rotator cuff tendon-bone interface and form a double-layer structure with the tendon-bone attachment point, play a stress dispersion role in the damaged area, and reduce the stress concentration of the tendon-bone interface during the repair process; by releasing the loaded connective tissue growth factor and calcium silicate in different regions, the regeneration of tendons, cartilage, and bone tissues is effectively promoted, and the healing of the tendon-bone interface is achieved simultaneously, which is beneficial to the repair of the rotator cuff tendon-bone interface.

[0118] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a rotator cuff patch, characterized in that: An oriented nanofiber patch co-spun by a synthetic biodegradable polymer and a natural bioactive protein of biological origin is prepared by electrospinning, calcium silicate nanoparticles are in situ co-precipitated at the distal end of the oriented nanofiber patch, and connective tissue growth factor is loaded at the proximal end of the oriented nanofiber patch to obtain the rotator cuff patch.

2. The method for preparing a rotator cuff patch according to claim 1, characterized in that: The following steps are involved: S1. Using synthetic biodegradable polymers and natural bioactive proteins from biological sources as raw materials and hexafluoroisopropanol as solvent, oriented nanofiber patches were prepared by electrospinning; S2. vertically immersing the distal end of the oriented nanofiber patch in a calcium nitrate tetrahydrate solution, and freeze-drying after the reaction; S3. The distal end of the nanofiber patch obtained in S2 is vertically immersed in a sodium silicate nonahydrate solution, and freeze-dried after the reaction to obtain a gradient patch loaded with calcium silicate at the distal end; S4. Vertically immerse the proximal end of the gradient patch prepared in S3 in a connective tissue growth factor solution, freeze-dry after the reaction, load the connective tissue growth factor on the proximal end of the gradient patch, and obtain the rotator cuff patch.

3. The method for preparing a rotator cuff patch according to claim 2, characterized in that: The synthetic biodegradable polymer includes polycaprolactone, a copolymer of polylactide and caprolactone or a copolymer of lactide and glycolide; and / or The biologically derived natural bioactive protein includes at least one of collagen, keratin, fibrin and elastin.

4. The method for preparing a rotator cuff patch according to claim 3, characterized in that: The mass ratio of the synthetic biodegradable polymer to the natural biologically active protein of biological origin is (8-13.5): (1-3).

5. The method for preparing a rotator cuff patch according to claim 2, characterized in that: During the electrospinning, the flow rate of the spinning solution is 2 mL / h, the working voltage is 14-16 kV, the distance between the syringe needle and the aluminum foil receiver is 14-16 cm, and the rotation speed of the aluminum foil receiver is 1500-2000 r / min.

6. The method for preparing a rotator cuff patch according to claim 2, characterized in that: The concentration of the calcium nitrate tetrahydrate solution is 10-40 mmol / L.

7. The method for preparing a rotator cuff patch according to claim 2, characterized in that: The concentration of the sodium silicate nonahydrate solution is 10-40 mmol / L.

8. The method for preparing a rotator cuff patch according to claim 2, characterized in that: The connective tissue growth factor solution has a concentration of 100-200 ng / mL.

9. A rotator cuff patch, characterized in that: Prepared according to the method according to any one of claims 1 to 8.

10. Use of the rotator cuff patch according to claim 9 in preparing tendon-bone interface damage repair material.

Citation Information

Patent Citations

  • Artificial rotator cuff patch capable of inducing tendon-bone gradient structure formation and preparation method thereof

    CN111359012A

  • Modular tissue-engineered bone-ligament-bone graft and preparation method thereof

    CN113893388A

  • Functional activity gradient bionic biological rotator cuff patch and preparation method thereof

    CN116236622A

  • Multi-layer bionic gradient structure rotator cuff patch and preparation method thereof

    CN117838932A

  • Rotator cuff patch and preparation method therefor

    WO2023143337A1